A Feasibility Evaluation of an Employee-led Brief Health Promotion Program to Promote Lifestyle Change in the Workplace - Koide, Keiko (J Prim Care Community Health, 2021)
BACKGROUND: In Japan, lifestyle-related diseases are a major issue. It is necessary to support employees in making lifestyle changes. As a result, this study intended to test and evaluate the feasibility of a brief lifestyle change program led by employees in the workplace. METHODS: A 2-group before-and-after test design was used, with employees from a plant in Japan as participants. Intervention was carried out by healthcare specialists for the Standard Intervention Group, while employees who previously received the same intervention performed it for the Employee-run Group. Data were collected twice with a questionnaire, provided in the first and last program sessions. The conditions of the participants during the intervention were compared. RESULTS: Of all the participants, 96 were in the Standard Intervention Group and 365 were in the Employee-run Group. The mean age did not differ significantly between the 2 groups. There was a significantly higher ratio of men and night shift workers in the Employee-run Group. Although a significantly smaller proportion of participants set shared behavioral goals for 3 people or self-monitored their lifestyle habits in the Employee-run Group, the lifestyle habits of self-checking, physical measurement, and other items for set goals did not differ. CONCLUSIONS: Participants in the Employee-run group completed components of the program to the same extent as those in the Standard Intervention Group, suggesting that this program is feasible. However, as the participation rate was lower in some components, improvements to the program and workbook are needed to make those components easier to complete.